2011
DOI: 10.1021/nl203763k
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial-Plasmonic Absorber Structure for High Efficiency Amorphous Silicon Solar Cells

Abstract: We show that a planar structure, consisting of an ultrathin semiconducting layer topped with a solid nanoscopically perforated metallic film and then a dielectric interference film, can highly absorb (superabsorb) electromagnetic radiation in the entire visible range, and thus can become a platform for high-efficiency solar cells. The perforated metallic film and the ultrathin absorber in this broadband superabsorber form a metamaterial effective film, which negatively refracts light in this broad frequency ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
180
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(186 citation statements)
references
References 30 publications
2
180
0
Order By: Relevance
“…In one recent scheme, it was demonstrated that if a high index absorptive material is incorporated into the structure, enhanced absorption can be achieved with a broad bandwidth. [65][66][67] As described in a classic optics book, 68 the reflected electrical components from an insulator/metal system can be expressed by the Fresnel coefficients of corresponding interfaces: if only the first two partial waves reflected back into air are considered,r r i~1 {ñ n i 1zñ n i represents the Fresnel coefficient of the air/insulator interface and r r i=m~ñ n i {ñ n m n n i zñ n m represents that of the insulator/metal interface (ñ n i andñ n m are the complex refractive indices of the insulator and the metal). The combined reflected wave is r r~r r i zr r i=m e i2h 1zr r ir r i=m e i2h ð1Þ…”
Section: Fp Mim Interferometermentioning
confidence: 99%
“…In one recent scheme, it was demonstrated that if a high index absorptive material is incorporated into the structure, enhanced absorption can be achieved with a broad bandwidth. [65][66][67] As described in a classic optics book, 68 the reflected electrical components from an insulator/metal system can be expressed by the Fresnel coefficients of corresponding interfaces: if only the first two partial waves reflected back into air are considered,r r i~1 {ñ n i 1zñ n i represents the Fresnel coefficient of the air/insulator interface and r r i=m~ñ n i {ñ n m n n i zñ n m represents that of the insulator/metal interface (ñ n i andñ n m are the complex refractive indices of the insulator and the metal). The combined reflected wave is r r~r r i zr r i=m e i2h 1zr r ir r i=m e i2h ð1Þ…”
Section: Fp Mim Interferometermentioning
confidence: 99%
“…Absorption with the randomly rough surfaces found in practice may be enhanced by adding photonic structures, even with modest spatial features which do not detract from the desired electrical properties of the layers [53]. Full photonic light trapping generally requires periodic structural elements with nanosized features (e.g., [54][55][56]) that are difficult to fabricate on a textile surface, but some degree of light trapping is still feasible even with disordered nanostructures and these do have less sensitivity than coherent light trapping structures to the acceptance angle of the light (e.g., [57,58]). …”
Section: Photovoltaic Fabricsmentioning
confidence: 99%
“…They also note that the location of metallic nanostructures (hence resultant LSPs) within or without the cell is important -it has been suggested that the performance of the cell may be improved by placing metallic nanostructures closer to the most active region of the cell, rather than just on the top surface of the cell [187]. It is possible that metallic films, hence SPPs may be used in a similar configuration for this purpose -Green and Pillai include a sketch of a proposed cell based on the work of Wang et al [188] which consists of a indium tin oxide layer (55 nm), the rear segment of which contains a 20 nm layer of Ag which covers 54% of the cell; this is followed by a 15 nm thick amorphous Si layer and then a 50 nm thick Ag layer as a rear reflector [187].…”
Section: Existing and Emerging Applicationsmentioning
confidence: 99%